Impacts of Company Support and Co-Creation Performance on Tourists' Satisfaction and Loyalty: An Experiment in The Mekong Delt - Ha, Van Dung (Journal of Reviews on Global Economics, 2020)
This study focuses on determining the impacts of company support and co-creation performance on tourists' satisfaction and how their satisfaction influences customer loyalty in the Mekong Delta. Based on a survey sample of 271 customers, Cronbach's alpha coefficient, exploratory factor analysis (EFA), confirmatory factor analysis (CFA) and structural equation model (SEM) are used for analysis. The results of the study indicated that the assurance most impacted on customers' satisfaction, followed by the responsiveness, empathy, reliability and physical facility. In addition, the customers' satisfaction is also a significant factor influencing customers' loyalty.